DETERMINATION OF PROTEIN IN THE GERM LINE CELLS OF ZIG-ZAG EEL Mastacembelus armatus, LACEPEDE 1800 (ACTINOPTERYGII: MASTACEMBELIDAE) FEMALE IN THE DIFFERENT REPRODUCTIVE PHASES: A HISTOCHEMICAL APPROACH - RAY, SUPRIYA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Mastacembelus armatus, is an indigenous fish species of southern Asia, which also resides in Indian subcontinent. This fish species is facing an alarming declining in their number in the last decade. Due to its moderate cost, it is mainly taken by the lower income group of people of the society. The proteins play very important role in the oocytes specially in external fertilization. Maternally inherited proteins play pivotal role in pattern formation as well as in the growth and development of the embryo. Microscopic ovarian features with respect to accumulation of protein of Mastacembelus armatus were analyzed. Samples were fixed in Carnoy’s fixative, mounted in 54° - 56° paraffin and cut into 8 µm-thick slices which were stained with Mercury – Bromphenol Blue (MBPB) method. After staining the thin sections with the thickness of approximately 8 µm were examined. Ovary of Mastacembelus armatus is extremely dynamic organ in which follicles underwent asynchronous development. The oocytes of ovary were observed in various phases. Accumulation of protein in the different stages of oocytes in zig-zageel with the advancement of spawning season shows a positive correlation.